Web phishing detection techniques: a survey on the state‐of‐the‐art, taxonomy and future directions. Issue 5 (23rd September 2020) - Vijayalakshmi, M.; Mercy Shalinie, S.; Yang, Ming Hour; U., Raja Meenakshi
Abstract : Internet dragged more than half of the world's population into the cyber world. Unfortunately, with the increase in internet transactions, cybercrimes also increase rapidly. With the anonymous structure of the internet, attackers attempt to deceive the end‐users through different forms namely phishing, malware, SQL injection, man‐in‐the‐middle, domain name system tunnelling, ransomware, web trojan, and so on. Amongst them, phishing is the most deceiving attack, which exploits the vulnerabilities in the end‐users. Phishing is often done through emails and malicious websites to lure the user by posing themselves as a trusted entity. Security experts have been proposing many anti‐phishing techniques. Till today there is no single solution that is capable of mitigating all the vulnerabilities. A systematic review of current trends in web phishing detection techniques is carried out and a taxonomy of automated web phishing detection is presented. The objective of this study is to acknowledge the status of current research in automated web phishing detection and evaluate their performance. This study also discusses the research avenues for future investigation.